2022
DOI: 10.1037/law0000370
|View full text |Cite
|
Sign up to set email alerts
|

An experimental manipulation of rapport and moral minimization within a criminal interview.

Abstract: Rapport is often viewed as the foundation of a successful investigative interview for its ability to increase cooperation and help interviewers obtain reliable and comprehensive information. However, rapport building may also serve to increase interpersonal influence and thereby might increase the power of other tactics, such as minimization. The present study experimentally manipulated both rapport building and moral minimization to test their combined effects on the reporting of crime-relevant details. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…In the absence of this, investigators may view science-based interview tactics as simply more “tools” for the proverbial “toolbox of interrogation tactics” (see Snook et al, 2020). We urge future researchers and trainers to consider this issue carefully and to explore the impact of direct instruction on practice, especially because few studies have examined the potency and reliability of interrogations that combine accusatorial-based methods with science-based approaches (cf., Vallano et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of this, investigators may view science-based interview tactics as simply more “tools” for the proverbial “toolbox of interrogation tactics” (see Snook et al, 2020). We urge future researchers and trainers to consider this issue carefully and to explore the impact of direct instruction on practice, especially because few studies have examined the potency and reliability of interrogations that combine accusatorial-based methods with science-based approaches (cf., Vallano et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Alison et al (2013) showed that rapport-building techniques were associated with positive interview outcomes, while Place and Meloy (2018) found that rapport strategies involving empathy best overcame interviewee resistance. More recent studies emphasize that supportive interviewing promotes rapport, cooperation, and informativeness on the part of adult suspects (e.g., Dianiska et al, 2021;Oleszkiewicz et al, 2023;Vallano et al, 2022). Interestingly, a concern with rapport throughout the interview is more effective than a focus on rapport-building only early in the interview (Baker-Eck & Bull, 2022).…”
Section: Rapport and Supportmentioning
confidence: 99%
“…Using the RSP, interviewers fostered greater responsiveness during the rapport-building phase, providing more details about a neutral event and sharing more information about themselves, suggesting that the children were more comfortable, trusting, and cooperative (Dianiska et al, 2021;Oleszkiewicz et al, 2023;Vallano et al, 2022). Similarly, the RP better promoted rapport during interviews with young suspected victims although interviewers tend to be more suspicious of young suspects than of alleged victims (Malloy & Lamb, 2010) and therefore rapport building with suspects is probably more challenging.…”
Section: Rapport Building and Maintenancementioning
confidence: 99%